Analisis Tindak Pidana Kekerasan Seksual Terhadap Anak di Bawah Umur Yang Dilakukan oleh Ayah kandung (Studi Putusan Pengadilan Bener Meriah Nomor 56/Pid.Sus/2019/PN Str) - Ulfa Taqwani; Ummi Kalsum; Arnita Arnita (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2022)
The Central Office for the Integrated Services for the Empowerment of Women and Children (P2TP2A) in Aceh noted that the highest number of victims of sexual violence were children. Aceh Province, precisely in Peace Village, Pintu Rime Gayo District, Bener Meriah Regency, a biological father had the heart to sexually abuse his own 14-year-old daughter 3 times in different years. Perpetrators of sexual violence are subject to criminal sanctions under Article 81 paragraph (1), paragraph (3) in conjunction with Article 76D of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection in conjunction with Law Number 17 of 2016 concerning Stipulation of Government Regulation in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection, namely by witnessing a prison sentence of 15 (fifteen) years. This research uses normative juridical research, namely library law research which can be done by examining library materials which are secondary data. This study focuses on legal materials that discuss the analysis of criminal acts of sexual violence against minors carried out by biological fathers (Bener Meriah Court Decision Study Number 56/Pid.Sus/2019/Pn Str). The results of the study are based on Law Number 35 of 2014 concerning child protection if the perpetrator of rape or obscenity is carried out by parents, guardians, child caregivers, educators, or educators, the penalty can be increased by 1/3 (one third) of the sentence. However, based on the Bener Meriah Court Decision Number 56/Pid.Sus/2019/Pn Str on the case of sexual violence by a biological father against his child, the perpetrator was sentenced to 15 (fifteen) years in prison without an additional third of the sentence. Sexual violence against children in Pintu Rime Gayo District, Bener Meriah Regency is caused by uncontrolled sources of information and socio-cultural factors which are still taboo with early age sex education. It is expected to increase the participation of the police, P2TP2A, BKBPP, Social Service / LK3, and stakeholders and punish perpetrators of sexual violence with the severest punishment to create a deterrent effect.